(untitled) - Wood, Oliver; (Cinematographer); Powell, John; 1972-; Ludlum, Robert; 1927-2001.; 1963-; Urban, Karl; Greengrass, Paul.; 1981-; Stiles, Julia; 1946-; et al. (Universal City, Calif., 2004)
Jason Bourne has abandoned his life as a CIA assassin and has been traveling beneath the agencys radar. He has been able to reconnect with Marie, the woman he loves. But Bourne is still haunted by vivid dreams and troubling memories of his days as a killer, and hes not really certain how much really happened and how much is a product of his imagination. When Bourne is led out of hiding by circumstances beyond his control, he must reconcile his past and present as he struggles to keep Marie out of harms way and foil an international incident with dangerous consequences.
Keywords: Bourne, Jason; (Fictitious character); Drama; Drama; Espionage; Drama; Assassins; Drama; Video recordings for the hearing impaired; Feature; Thriller; Feature films